1975
DOI: 10.33584/jnzg.1975.37.1440
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Herbage Utilization ~ on Pasture Production and Animal Performance

Abstract: An attempt is made to establish a relationship between herbage utilization, pasture production, and animal performance per unit area. When pastures are rotationally grazed, it appears that the highest pasture yield and animal production per unit area will result only if feed demand is closely matched with supply so that little stubble is left after grazing. Experimental data indicate that the aim should be to achieve at least 60% single grazing utilization of the total herbage on offer as long as in so doing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Moreover, in paddocks where subterranean clover populations are low, and therefore unproductive, spelling pastures earlier than normal lamb weaning dates can be used to increase clover seed banks in the soil (Litherland et al ., ; Ates et al ., ). However, while the effects of SR on per head and per hectare production are well understood for perennial ryegrass–white clover pastures (Smetham, ; Harris, ; Curll et al ., ; Hernández Garay et al ., ), less information is available for non‐irrigated pastures based on annual legumes. In particular, the effect of a fixed SR on liveweight gain as pasture quality and mass decline towards summer due to the onset of dry conditions and annual clover senescence has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in paddocks where subterranean clover populations are low, and therefore unproductive, spelling pastures earlier than normal lamb weaning dates can be used to increase clover seed banks in the soil (Litherland et al ., ; Ates et al ., ). However, while the effects of SR on per head and per hectare production are well understood for perennial ryegrass–white clover pastures (Smetham, ; Harris, ; Curll et al ., ; Hernández Garay et al ., ), less information is available for non‐irrigated pastures based on annual legumes. In particular, the effect of a fixed SR on liveweight gain as pasture quality and mass decline towards summer due to the onset of dry conditions and annual clover senescence has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…Brougham (1959) found no difference in winter and spring production from swards grazed to either 7.5 or 2.5 cm, and Tainton (1974) reported a lower rate of senescence and decomposition and a higher regrowth rate for pastures grazed to 2.5 cm in the late spring than for those with large amounts of stubble left. Other work reviewed by Smetham (1975) showed that overgrazing of perennial ryegrass did not occur until less than 2 cm stubble was left. This could explain the depression in yield reported by Harris and Brown (1970) for pastures grazed to 1.25 cm every fortnight over winter and early spring.…”
Section: Pasture a Vailability R Esidue And R Egrowthmentioning
confidence: 96%
“…What is not as often appreciated is that productivity is diminished by understocking too (Morris 1969). As Smetham (1976) pointed out, there must be a balance point-an optimum stocking rate at which pasture produces at or near máximum, and this will occur at a rate which is neither too high ñor too low. Evidence that this is so is seen in the results of Mott (1960) who put together the results of some 24 beef stocking rate experiments, and perhaps most pointedly by Vickery (1972).…”
Section: Guidelines When Set-stockingmentioning
confidence: 99%